RESEARCH OF PARAMETERS OF ENCODING OF THE ALGORITHM WITH VARIABLE FRAGMENTATION OF THE UNIT - K. O. Zakharova (Системный анализ и прикладная информатика, 2018)
This article presents recommendations on the selection of parameters of the encryption algorithm with variable fragmentation of the block, developed on the basis of a study of the obtained results of the algorithm with different encryption parameters (p and q). The investigation of the algorithm’s work with variable block fragmentation in the selection of various parameters is performed using pseudorandom sequence testing techniques, including statistical and graphical tests on encrypted sequences using various parameters in a binary representation. The statistical test is selected from a selection of D. Knuth tests, namely the correlation check. As a graphic test, we constructed a k-gram distribution. Based on the results of the study of the operation of the algorithm with various encryption parameters (p and q), the following recommendations for the selection of parameters are formulated: p and q are mutually prime numbers, the partition of the sequence into p-subblocks is greater than the partition into q-subblocks (p > q).